Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To show that \(f^{-1}(x) = \frac{7x - 7}{5}\) is the inverse of \(f(x) = \frac{5}{7}x + 1\), we need to verify the following two compositions:
1. \((f^{-1} \circ f)(x) = x\)
2. \((f \circ f^{-1})(x) = x\)
We'll start with the first composition.
### 1. \((f^{-1} \circ f)(x)\)
[tex]\[ \begin{aligned} (f^{-1} \circ f)(x) & = f^{-1}(f(x)) \\ & = f^{-1}\left(\frac{5}{7}x + 1\right). \end{aligned} \][/tex]
Next, we substitute the expression for \(f(x)\) into the inverse function \(f^{-1}(y) = \frac{7y - 7}{5}\).
[tex]\[ \begin{aligned} f^{-1}\left(\frac{5}{7}x + 1\right) &= \frac{7 \left(\frac{5}{7}x + 1\right) - 7}{5}\\ & = \frac{7 \cdot \frac{5}{7}x + 7 \cdot 1 - 7}{5}\\ & = \frac{5x + 7 - 7}{5}\\ & = \frac{5x}{5}\\ & = x. \end{aligned} \][/tex]
Thus, we have shown that \((f^{-1} \circ f)(x) = x\).
### 2. \((f \circ f^{-1})(x)\)
[tex]\[ \begin{aligned} (f \circ f^{-1})(x) & = f(f^{-1}(x)) \\ & = f\left(\frac{7x - 7}{5}\right). \end{aligned} \][/tex]
Now, substitute the expression for \(f^{-1}(x)\) into the function \(f(x) = \frac{5}{7}x + 1\):
[tex]\[ \begin{aligned} f\left(\frac{7x - 7}{5}\right) &= \frac{5}{7} \left(\frac{7x - 7}{5}\right) + 1\\ & = \frac{5 \cdot (7x - 7)}{7 \cdot 5} + 1\\ & = \left(\frac{7x - 7}{7} \right) + 1\\ & = x - 1 + 1\\ & = x. \end{aligned} \][/tex]
Thus, we have shown that \((f \circ f^{-1})(x) = x\).
Having verified both compositions, we can conclude that [tex]\(f^{-1}(x) = \frac{7x - 7}{5}\)[/tex] is indeed the inverse of [tex]\(f(x) = \frac{5}{7}x + 1\)[/tex].
1. \((f^{-1} \circ f)(x) = x\)
2. \((f \circ f^{-1})(x) = x\)
We'll start with the first composition.
### 1. \((f^{-1} \circ f)(x)\)
[tex]\[ \begin{aligned} (f^{-1} \circ f)(x) & = f^{-1}(f(x)) \\ & = f^{-1}\left(\frac{5}{7}x + 1\right). \end{aligned} \][/tex]
Next, we substitute the expression for \(f(x)\) into the inverse function \(f^{-1}(y) = \frac{7y - 7}{5}\).
[tex]\[ \begin{aligned} f^{-1}\left(\frac{5}{7}x + 1\right) &= \frac{7 \left(\frac{5}{7}x + 1\right) - 7}{5}\\ & = \frac{7 \cdot \frac{5}{7}x + 7 \cdot 1 - 7}{5}\\ & = \frac{5x + 7 - 7}{5}\\ & = \frac{5x}{5}\\ & = x. \end{aligned} \][/tex]
Thus, we have shown that \((f^{-1} \circ f)(x) = x\).
### 2. \((f \circ f^{-1})(x)\)
[tex]\[ \begin{aligned} (f \circ f^{-1})(x) & = f(f^{-1}(x)) \\ & = f\left(\frac{7x - 7}{5}\right). \end{aligned} \][/tex]
Now, substitute the expression for \(f^{-1}(x)\) into the function \(f(x) = \frac{5}{7}x + 1\):
[tex]\[ \begin{aligned} f\left(\frac{7x - 7}{5}\right) &= \frac{5}{7} \left(\frac{7x - 7}{5}\right) + 1\\ & = \frac{5 \cdot (7x - 7)}{7 \cdot 5} + 1\\ & = \left(\frac{7x - 7}{7} \right) + 1\\ & = x - 1 + 1\\ & = x. \end{aligned} \][/tex]
Thus, we have shown that \((f \circ f^{-1})(x) = x\).
Having verified both compositions, we can conclude that [tex]\(f^{-1}(x) = \frac{7x - 7}{5}\)[/tex] is indeed the inverse of [tex]\(f(x) = \frac{5}{7}x + 1\)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.